Building Information Modeling in the Architecture and Construction Industry - Jerome Jordan Faz Famadico (Advances in Technology Innovation, 2023)
This study aims to investigate the benefits, risks, barriers, and approaches of building information modeling (BIM) implementation in the architecture, engineering and construction (AEC) industries. Descriptive research methods such as surveys and key informant interviews are used to gather data. Respondents in the survey come from different AEC companies and are selected with a purposive sampling method. Descriptive statistics and one-way analysis of variance (ANOVA) are utilized to analyze the data. The narrative analysis method is also performed to validate the research findings through a desk review of secondary data. The result shows that the major benefit of BIM is earlier and more accurate design visualization, while the main risk is accountability and control of data entry into the model. Moreover, the major barrier to BIM implementation is the high acquisition cost, and the most recommended approach is to increase the availability of BIM technology.